2021
DOI: 10.1111/dth.14766
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of teledermoscopy in the era of telemedicine

Abstract: Teledermoscopy is a novel diagnostic tool for the prevention, diagnosis, and treatment of skin disease when direct visualization of lesions is difficult. It is an economically viable option that can complement telehealth visits and that providers can utilize to identify melanocytic lesions and optimize care with diagnostic accuracy comparable to face-to-face (FTF) diagnosis. Teledermoscopy is invaluable in monitoring chronic conditions that require frequent follow-up and treatment optimization.Inclusion of cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 14 publications
(66 reference statements)
0
24
0
Order By: Relevance
“…Maps can be constructed from measurements done directly on the patient prior to lesion excision in cases where extensive surgery may be needed to remove the entire tumor in one step. VOCT and dermoscopic observations in conjunction with artificial intelligence can be used to diagnose difficult skin lesions and improve the clinical utility of teledermoscopy [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maps can be constructed from measurements done directly on the patient prior to lesion excision in cases where extensive surgery may be needed to remove the entire tumor in one step. VOCT and dermoscopic observations in conjunction with artificial intelligence can be used to diagnose difficult skin lesions and improve the clinical utility of teledermoscopy [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nouri et al reported lower telehealth use in Black/African American and Latinx patients in an urban safety net, highlighting the role of entrenched systemic racism in health care[ 21 ]. Health system level: Very few health care systems had robust telehealth use before the pandemic except tele-dermatology [ 22 ] and organizations like Kaiser Permanente [ 23 , 24 ] that had implemented telehealth visits before the pandemic. At the health system level, the clinic workflows designed for in-person visits need optimization for telehealth to ensure that critical care is not missed, and team-based care is seamlessly integrated into a telehealth model.…”
Section: Barriers To Telehealth Can Be Classified Into Four Different Levels Requiring Multilevel Approaches To Address Disparitiesmentioning
confidence: 99%
“…On the other hand. A hardware upgrade can also be a solution to this problem, there have been products such as the attachable dermatoscope that are made to fit mobile phones [33], this should theoretically solve the mobile image quality problem as well. However, its image quality will still have to be tested against the professional camera skin lesion images to prove its authenticity.…”
Section: Limitations and Future Workmentioning
confidence: 99%